2023
DOI: 10.1021/acs.orglett.3c00873
|View full text |Cite
|
Sign up to set email alerts
|

Ruthenium-Catalyzed Ligand-Enabled Regiodivergent Difluoroallylation of Aryl C–H Bonds

Abstract: The gem-difluoroallyl group is a sought-after structural motif commonly found in pharmaceutical compounds. Despite its appeal, achieving a controlled synthesis of both α,αand γ,γ-difluoroallylated compounds has proven to be a challenging task. This study presents a new approach to difluoroallylation, which utilizes a regiodivergent C−H bond reaction catalyzed by ruthenium catalysis. This method enables the meta and ortho C−H α,αand ortho C−H γ,γ-difluoroallylation of arenes using 3-bromo-3,3difluoropropenes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…Meanwhile, ruthenium-catalyzed m -(sp 2 )-H functionalization has attracted a great deal of attention. Ackermann, Li, Zhang, and others have made appreciable progress in this field. Through detailed mechanistic studies, it has been confirmed that the ruthenium-catalyzed remote transformation operates via the distinctive mechanism of SET .…”
mentioning
confidence: 99%
“…Meanwhile, ruthenium-catalyzed m -(sp 2 )-H functionalization has attracted a great deal of attention. Ackermann, Li, Zhang, and others have made appreciable progress in this field. Through detailed mechanistic studies, it has been confirmed that the ruthenium-catalyzed remote transformation operates via the distinctive mechanism of SET .…”
mentioning
confidence: 99%
“…Ruthenium catalysis has made some progress in the construction of multisubstituted alkenes . Some of these representative figures were Krische, Ackermann, Zhang, Li, and others . In 2005, Inoue developed ruthenium-catalyzed arylation of 2-alkenylpyridines with aryl bromides, affording Z products exclusively (Scheme B).…”
mentioning
confidence: 99%
“…1B). The synthetic methods of difluoromethylene compounds are relatively abundant, including the deoxyfluorination of ketones, 10 the nucleophilic transformation of difluoroenolates 11–13 and related nucleophiles, 14,15 regioselective difluoroallylation, 16–20 the addition of difluoroalkyl radical, 21–23 and the transfer of difluorocarbene. 24,25 The synthesis of tetrafluoroethylene bridged compounds has been achieved by the double deoxyfluorination of 1,2-diketone species; however, the reaction requires a large amount of corrosive fluorination reagents.…”
mentioning
confidence: 99%